The confusion in understanding salvation in church religion by African Christian people as it relates to Salvation in African Traditional religion hampers the building up of the local church - Nel, Malan (University of Pretoria, 2013)
Dissertation (MA (Practical Theology))--University of Pretoria, 2007.